Clinical significance of dermal backflow on lymphoscintigraphy in patients with lower limb edema - Areej Aijaz; Tanzil Sajid; Aamna Hassan (Journal of the Pakistan Medical Association, 2023)
Chronic blockage of the lymphatic system due to functional or anatomical causes results in lymphoedema which results in swelling due to accumulation of lymphatic fluid in the soft tissue. Lymphoedema commonly affects the upper and lower limbs but may be seen in the neck, chest wall, abdomen and genitalia. Lymphoscintigraphy is non-invasive and maps the lymphatic channels thereby indicating location of blockage along the lymphatic pathways. Blockage of lymphatic channels may lead to back pressure resulting in dermal backflow. We present a case of dermal backflow in bilateral lymphoedema. Keywords: lymphoscintigraphy, dermal backflow, lymphedema